AN ANALYSIS OF FLOUTING MAXIM IN PEP GUARDIOLA’S PRE-MATCH & POST MATCH PRESS CONFERENCES IN EPL 2023/2024 - Dohan Zuhudiyanto; Ahmad Juma Khatib Nur Ali (Triwikrama: Jurnal Ilmu Sosial, 2024)
Communication is important in our daily lives; some people sometimes ruin conversation by speaking non sense or talking out of topic. Avoiding people misunderstanding can improve our conversation quality. Therefore, this research only focuses on analysing flouting maxims. The main objective of this research is to find out how often Pep Guardiola flout the maxim and to find out kind of maxims that have most appearances. The qualitative method and documentation technique is used to find data in Pep Guardiola pre-match and post-match press conference interview in EPL 2023/2024 at games week 26, 27, 28, 30 & 31. This research showed that all of the flouting maxims are founded. All of them are flouting maxim of quality (14 data), flouting maxim of quantity (5), flouting maxim of relation (13) and flouting maxim of manner (2). Based on the data in this research the most dominant is flouting maxim of quantity and the less appearances is flouting maxim of manner. Keywords: Flouting Maxim, Pep Guardiola, press conference.